Bacteriological analysis of well water samples in sagamu (2011)
Majority of the population in semi-urban and urban areas of Nigeria depend on wells as their source of water supply. Due to increasing cases of water-borne diseases in recent times, this study was carried out to examine the microbial quality of well water in Sagamu, Nigeria as a way of safeguarding public health against water borne diseases. Water samples from a total of forty wells, covered and uncovered from four different locations of varying socio economic and demographic status were assessed for their bacteriological quality using serial dilution to obtain total bacteria count and the multiple tube fermentation technique to determine the coliform count using the most probable number method. Positive tubes of the presumptive test were further cultured on appropriate solid media. The organisms isolated were further characterized using standard procedures. The result of the study revealed that all the wells were grossly contaminated with bacteria pathogens such as Klebsiella spp (95%), Escherichia coli (72%) and Salmonella typhi (32.5%). Comparatively, the uncovered wells were more highly contaminated with bacteria pathogens than the covered well especially in the highly populated areas. All the water samples exceeded the standard limit of the most probable number (MPN) per 100ml set for untreated drinking water. This result highlight the fact that most well water in Sagamu metropolis are not safe microbiologically for drinking without additional treatment such as boiling or disinfection and this could lead to outbreak of water borne diseases. Good and proper environmental and personal hygiene must be maintained especially by the users of those wells to prevent their contamination with bacterial pathogens.